2011
DOI: 10.4142/jvs.2011.12.4.387
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography and intraoral radiography for diagnosis of dental abnormalities in dogs and cats

Abstract: The development of veterinary dentistry has substantially improved the ability to diagnose canine and feline dental abnormalities. Consequently, examinations previously performed only on humans are now available for small animals, thus improving the diagnostic quality. This has increased the need for technical qualification of veterinary professionals and increased technological investments. This study evaluated the use of cone beam computed tomography and intraoral radiography as complementary exams for diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
(26 reference statements)
2
21
0
Order By: Relevance
“…Because of the severe overlap of anatomic structures in the region of the maxillary premolar teeth for the Rad, Pano, and 3-D methods, it was not surprising to find significantly improved diagnostic yield for the Slices method for all evaluated teeth in that region, which confirmed the findings of a previous study. 15 However, the fact that similar results would also be found for the maxillary canine teeth was rather unexpected because overlap of anatomic structures is limited in that region. The finding was further intriguing because even Pano scores were higher for the maxillary canine teeth when compared with scores for the Rad method, which raised the question of whether the bisecting angle used for dental radiographs might obscure anatomic detail and, potentially, also associated pathological changes in brachycephalic breeds.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Because of the severe overlap of anatomic structures in the region of the maxillary premolar teeth for the Rad, Pano, and 3-D methods, it was not surprising to find significantly improved diagnostic yield for the Slices method for all evaluated teeth in that region, which confirmed the findings of a previous study. 15 However, the fact that similar results would also be found for the maxillary canine teeth was rather unexpected because overlap of anatomic structures is limited in that region. The finding was further intriguing because even Pano scores were higher for the maxillary canine teeth when compared with scores for the Rad method, which raised the question of whether the bisecting angle used for dental radiographs might obscure anatomic detail and, potentially, also associated pathological changes in brachycephalic breeds.…”
Section: Discussionmentioning
confidence: 61%
“…Studies conducted in veterinary 15 and human 16 dentistry found that CBCT imaging is superior to intraoral dental radiography with regard to general criteria such as duration of examination, anesthesia time, radiation exposure, and associated risks for patients. Authors of multiple morphometric studies 10,16,17 further concluded that a tridimensional imaging modality, such as CBCT, is better suited for identification of anatomic landmarks than are 2-D imaging modalities, such as dental radiography.…”
Section: Discussionmentioning
confidence: 99%
“…To date, available literature has concentrated on the use of CBCT for dental abnormalities in dogs, cats and rabbits [1518]. …”
Section: Introductionmentioning
confidence: 99%
“…I ntraoral dental radiography is the established gold standard for canine dental imaging. More recently added diagnostic values of conventional computed tomography (CT) and cone beam CT have been demonstrated in people and recently also dogs and cats . CT is an efficient and widely used imaging modality for the canine head.…”
Section: Introductionmentioning
confidence: 99%